Endovascular management of aortocaval fistula complicating abdominal aortic aneurysm presenting as an acute renal failure - Esmat, Habib Ahmad (Ann Med Surg (Lond), 2021)
INTRODUCTION: Aortocaval fistulas (ACFs) are a rare complication of abdominal aortic aneurysm (AAA), associated with high morbidity and mortality. It is thought that increased tension in the walls of large aneurysms can cause an inflammatory reaction resulting in adhesion to the adjacent vein and culminating in necrosis of the adherent layers and fistula formation. PRESENTATION OF CASE: A 70-year-old male was referred from a local state center to the emergency department of our hospital, complaining of weakness and oliguria for two days. The laboratory analysis yielded high urea and creatinine levels, indicating an acute renal failure. Computed tomography images showed an aortocaval fistula complicating infrarenal abdominal aortic aneurysm. The patient was successfully managed with endovascular intervention. DISCUSSION: Aortocaval fistulas generally affect elderly men with an average age of 65 years. The diagnosis is often delayed because of the variable clinical manifestations, which increases the difficulties in treatment. Conventional surgical intervention has high mortality rates. However, endoleaks and paradoxical pulmonary embolism are the main concerning complications of endovascular treatment. CONCLUSION: Spontaneous aortocaval fistulas are a rare, but potentially life-threatening complication of abdominal aortic aneurysm with myriad clinical manifestations. Early diagnosis and management can directly affect the prognosis and outcome. Modern non-invasive diagnostic imaging can help timely diagnosis and provide a road map for the treatment plan. Endovascular repair is the first choice of treatment. However, a high incidence and persistence of endoleak with the endovascular approach requires caution and a close long time follow up.